2012
DOI: 10.1590/s1415-43662012001200012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of drying of basil leaves (Ocimum basilicum L.) in the infrared

Abstract: The objective of this paper was to model the drying curves of the leaves of basil (Ocimum basilicum L.) in the infrared at temperatures of 50, 60, 70 and 80 ºC and to evaluate the influence of drying temperature on the color of dried leaves. Drying was conducted in infrared dryer with temperature and greenhouse air circulation. Experimental data were fitted to eight mathematical models. The magnitude of the coefficient of determination (R²), the mean relative error (P), the estimated mean error (SE) and chisqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
(13 reference statements)
4
7
0
Order By: Relevance
“…Consequently, chlorophyll degradation occurs and this process varies also according to pH and variations of temperature, light and oxygen in the sample (Bohn & Walczyk, 2004). Similar behavior was reported by Reis et al (2012) in the convective drying of basil (Ocimum basilicum L.) leaves, which caused degradation of chlorophylls with the increase in drying temperature.…”
Section: Characterization Of Pigments and Colorimetric Parameterssupporting
confidence: 73%
“…Consequently, chlorophyll degradation occurs and this process varies also according to pH and variations of temperature, light and oxygen in the sample (Bohn & Walczyk, 2004). Similar behavior was reported by Reis et al (2012) in the convective drying of basil (Ocimum basilicum L.) leaves, which caused degradation of chlorophylls with the increase in drying temperature.…”
Section: Characterization Of Pigments and Colorimetric Parameterssupporting
confidence: 73%
“…Figure 1 shows that constant k of the model of Midilli increases in absolute values with increasing temperature, since higher temperatures lead to higher drying rates; however, the other coefficients of the model of Midilli (a, n and b) did not show a clear trend as a function of drying temperatures. Reis et al (2012) also reported increased k constant with increasing temperature when drying basil leaves.…”
Section: Drying Kineticsmentioning
confidence: 87%
“…Such models include the Midilli, Page, Thompson, Verma, Henderson and Pabis, logarithmic, two-term, two-term exponential, Newton, Wang and Singh, diffusion approximation, and Valcam models (Mohapatra & Rao, 2005;Kashaninejad et al, 2007;Goneli et al, 2009;Corrêa et al, 2010;Resende et al, 2011;Prates et al, 2012;Reis et al, 2012;Siqueira et al, 2012a;Siqueira et al, 2012b;Isquierdo et al, 2013;Santos et al, 2013). Fernanda P. da Silva, Valdiney C. Siqueira, Guilherme A. Quinzani, et al Eng.…”
Section: Introductionmentioning
confidence: 99%